Strategi untuk Meningkatkan Kesehatan Fungsional dan Kesejahteraan Fakultas dan Staf Universitas Kamboja - Lee Fergusson Fergusson (Warmadewa University, 2020)
The range of outcomes and published record on the Transcendental Meditation technique across 50 years of research in education, business, and government makes its application unique. Its association with health and relation to an individual’s quality-of-life have also made the technique useful in some developing countries. Data related to application of the technique to higher education in Cambodia have been accruing since the early 1990s. The 26-year research program begun by these authors associated with Transcendental Meditation and non-verbal intelligence, post-traumatic stress disorder, anxiety, depression, learning, memory, and personality in university students, as well as its collective effects on economic and social indicators and reductions in socio-political violence and crime, makes for an uncommonly rich body of knowledge in a country where empirical research has been rare. Indeed, the early studies in this research program represented among the first published research on higher education since the 1960s, after which Cambodia was plunged into civil war, genocide, and ongoing social turmoil and political conflict until 1993. The present study, which is a modified version of a study previously published in ASEAN Journal of Education, extends this research program to include a preliminary investigation of the practice of Transcendental Meditation by faculty and staff in three regional Cambodian universities and examines its impact on health and well-being. Findings generated by a concurrent, quasi-experimental mixed methods design suggest the practice may be of benefit to university personnel as measured by physical mental and social health, perceived health, self-esteem, anxiety, and depression, among other quality-of-life variables, thereby adding to previous results associated with higher education in this increasingly important south-east Asian nation.